Missed Nursing Care Among Patients With Dementia During Hospitalization: An Observation Study - Evripidou, Melina; Merkouris, Anastasios; Charalambous, Andreas; Karanikola, Maria; Zavrou, Rafailia; Papastavrou, Evridiki (My University, 2021)
Patients with dementia (PwD) are characterized as a vulnerable group as they are unable to communicate their needs, putting them at risk for care omissions. The current study aimed to explore care toward PwD and detect if any aspects of care are omitted. An observation study was conducted in three medical-surgical adult wards of an acute general hospital. Data were collected by an observer, through field notes, and were analyzed with content analysis. A face scale was used to assess PwD's mood. Thirteen PwD were observed for 90 hours. Four thematic areas were identified: (a) Unmet Fundamental Patient Needs, (b) Human Right to Dignity and Respect, (c) Communication Deficiencies, and (d) Implementation of Nursing Interventions. Nurse-patient contact lasted from 5 to 7 minutes and numerous care omissions were noted. The face scale assessment revealed that most PwD looked very sad after nursing care. This study enriches insight for the care of PwD during hospitalization and emphasizes the need for health care workers' education and support. [Research in Gerontological Nursing, 14(3), 150-159.].
Keywords: Nursing Homes; End of Life Care; Mcgill Pain Questionnaire